Questionnaires for Evaluation the Nutritional Status of Cancer Patients - Claudia Raluca BALASA VIRZOB; Melania Camelia FIZEDEAN; Corina VERNIC (Applied Medical Informatics)
The evaluation of the nutritional status of the cancer patient is necessary during the oncological follow-up. The use of assessment tools becomes reliable in the nutritional status of these patients, providing accurate information on the patient's situation. The aim of this study was to identify valid and reliable tools in the assessment of the nutritional status of cancer patients. A scope assessment was performed to search for medical articles in the last four years. A total of 552 articles were initially identified, which were examined, reaching a final selection of 13 studies. The most commonly used tool for nutritional assessment was the Patient-Generated Subjective Global Assessment. Questionnaires for evaluation the nutritional status vary from qualitative assessments to quantitative measurements, and can be subjective or objective.